The Effect of Preceding Self-Control on Prosocial Behaviors: The Moderating Role of Awe - Li, Jin; Li, Anke; Sun, Yu; Li, Hui’ e; Liu, Lei; Zhan, Youlong; Fan, Wei; Zhong, Yiping (Frontiers in Psychology, 2019)
The exertion of self-control is known to result in subsequent detrimental effects on prosocial behaviors. Moreover, certain studies have demonstrated that positive emotions could drive people to allocate more attentional resources for conducting prosocial behaviors. However, whether and how awe - one important type of positive incidental emotion - moderates the effect of exerting self-control on subsequent prosocial behaviors remains unclear yet. The anonymous economic dictator game is an effective index of prosocial behaviors. We examined the influence of exerting self-control on prosocial behavior and the moderating role of awe on the effect of exerting self-control on prosocial behaviors in two experiments (N = 280). We adopted the incongruent Stroop task to induce the exertion of self-control and participants were required to allocate money to others in the anonymous dictator game (Experiment 1). We used the narrative recall task paradigm to elicit the emotion of awe during the interval between Stroop tasks and the dictator game (Experiment 2). Results indicated that the exertion of self-control was detrimental to prosocial behaviors and awe weakened the detrimental effects of exerting self-control on prosocial behavior. We interpreted these results in terms of the Protective Inhibition of Self-regulation and Motivation (PRISM) model.